2017
DOI: 10.1002/14651858.cd006842.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating devices for airway clearance in people with cystic fibrosis

Abstract: There was no clear evidence that oscillation was a more or less effective intervention overall than other forms of physiotherapy; furthermore there was no evidence that one device is superior to another. The findings from one study showing an increase in frequency of exacerbations requiring antibiotics whilst using an oscillating device compared to positive expiratory pressure may have significant resource implications. More adequately-powered long-term randomised controlled trials are necessary and outcomes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 66 publications
(1 reference statement)
2
60
1
5
Order By: Relevance
“…However, even though a recent study in bronchiectasis observed such an effect, 40 it was rarely found with other airway clearance techniques in subjects with CF. [41][42][43] In this systematic review, we did not find any benefit of IPV on airway clearance, contrary to what was demonstrated in subjects with Duchenne muscular dystrophy. 19 The wet weight of sputum increased with IPV compared to other airway clearance techniques in 1 study including 3 daily sessions, 30 but the combination of IPV and autogenic drainage was as efficient on sputum as autogenic drainage used alone.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…However, even though a recent study in bronchiectasis observed such an effect, 40 it was rarely found with other airway clearance techniques in subjects with CF. [41][42][43] In this systematic review, we did not find any benefit of IPV on airway clearance, contrary to what was demonstrated in subjects with Duchenne muscular dystrophy. 19 The wet weight of sputum increased with IPV compared to other airway clearance techniques in 1 study including 3 daily sessions, 30 but the combination of IPV and autogenic drainage was as efficient on sputum as autogenic drainage used alone.…”
Section: Discussioncontrasting
confidence: 93%
“…These new techniques, however, are not always supported by well-designed, randomized studies. [5][6][7] Intrapulmonary percussive ventilation (IPV) derives from high-frequency percussive ventilation, which was initially applied to treat respiratory failure after smoke inhalation or burns. [8][9][10][11] It is a pressure-limited, time-cycled, high-frequency mode of ventilation that delivers sub-physiologic tidal volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapy with a device creating oscillating positive expiratory pressure, the Flutter®, is an established form of airway clearance in CF and is equally effective to other airway clearance techniques [16]. The Flutter® improves mucus clearance mechanisms in CF by increasing PEF and creating an expiratory airflow bias, [17] as well as reducing sputum mechanical impedance [18].…”
Section: Introductionmentioning
confidence: 99%
“…PEP devices that contain an expiratory oscillatory component such as the Acapella, RC Cornet, Flutter, Aerobika (Trudell Medical International, Ontario, Canada), Lung Flute (Medical Acoustics, Buffalo, NY), and Quake (Thayer Medical Corporation, Tucson, AZ) are all theoretically useful for patients with tenacious secretions, as the frequency of oscillations are hypothesized to loosen secretions and reduce mucus viscoelasticity. 9,66 They are similar to the PEP device, in that they involve breathing against an expiratory resistance, but the resistance is intermittent or interrupted by a ball valve, lever, or collapsible tubing, such that oscillations of variable frequency (depending on device or use) are transmitted to the airways during the expiratory cycle. An airflow bias is created as the oscillations increase the expiratory airflow.…”
Section: Oscillating Pep Including Bubble Pepmentioning
confidence: 99%
“…6 The best evidence from a plethora of early, underpowered, short-term studies, typically crossover design and 1 to 14 days in length, has been synthesized in five Cochrane reviews related to ACTs for CF, published between 2000 and 2011. [7][8][9][10][11] All conclude that there is currently insufficient evidence to suggest superiority of any one technique over another. The earliest of these reviews, recently updated, compared airway clearance to no treatment in people with CF.…”
mentioning
confidence: 99%